2011
DOI: 10.1016/j.jcrs.2010.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diclofenac sodium combined with nuclear rotation on the prevention of posterior capsule opacification: Two-year follow-up

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Estudios científicos de laboratorio realizados en animales sugieren que el uso de fármacos antinfla-matorios no esteroideos después de la intervención de cirugía de cataratas puede reducir la incidencia de OCP (Duong, Westfield y Chalkley, 2007;Inan et al, 2006;Yao et al, 2011). Flach y Dolan (2000) realizaron un estudio prospectivo aleatorizado para determinar la incidencia de OCP tres años después de la intervención, tras tratamientos con diclofenaco al 0,1 % y ketorolaco al 0,5 %, administrados por vía oftálmica cuatro veces al día, durante 30 días.…”
Section: Fármacosunclassified
“…Estudios científicos de laboratorio realizados en animales sugieren que el uso de fármacos antinfla-matorios no esteroideos después de la intervención de cirugía de cataratas puede reducir la incidencia de OCP (Duong, Westfield y Chalkley, 2007;Inan et al, 2006;Yao et al, 2011). Flach y Dolan (2000) realizaron un estudio prospectivo aleatorizado para determinar la incidencia de OCP tres años después de la intervención, tras tratamientos con diclofenaco al 0,1 % y ketorolaco al 0,5 %, administrados por vía oftálmica cuatro veces al día, durante 30 días.…”
Section: Fármacosunclassified
“…We demonstrated that postoperative long-term use of topical ketorolac drops in pediatric cataract patients with intact posterior capsules prevented PCO formation [ 10 ]. Similarly, hydrodissection using diclofenac sodium prevented PCO up to two years postoperatively [ 11 ]. Moreover, a recent in vitro and in vivo study has demonstrated that IOLs loaded with ketorolac reduce the tendency for adhesion of LECs, and no PCO signs were encountered [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors have already been identified for the progression of PCO, which include edge design, intraocular lens design, haptic design, and lens material [4,7] . Currently, there are several techniques introduced for preventing PCO, such as intraocular lens material, surgical techniques, and therapeutic agents [8][9][10] . Acrylic materials show a low ability to stimulate the proliferation of cells in the capsular bag [11] and intraocular lenses with sharp edge design might assist in inhibiting migration of lens epithelial cells [12] ,…”
Section: Introductionmentioning
confidence: 99%